Differential roles of migratory and resident DCs in T cell priming after mucosal or skin HSV-1 infection - Lee, Heung Kyu (The Rockefeller University Press, 2009)
Although mucosal surfaces represent the main portal of entry for pathogens, the mechanism of antigen presentation by dendritic cells (DCs) that patrol various mucosal tissues remains unclear. Instead, much effort has focused on the understanding of initiation of immune responses generated against antigens delivered by injection. We examined the contributions of migratory versus lymph node–resident DC populations in antigen presentation to CD4 and CD8 T cells after needle injection, epicutaneous infection, or vaginal mucosal herpes simplex virus (HSV) 1 infection. We show that upon needle injection, HSV-1 became lymph-borne and was rapidly presented by lymph node–resident DCs to CD4 and CD8 T cells. In contrast, after vaginal HSV-1 infection, antigens were largely presented by tissue-derived migrant DCs with delayed kinetics. In addition, migrant DCs made more frequent contact with HSV-specific T cells after vaginal infection compared with epicutaneous infection. Thus, both migrant and resident DCs play an important role in priming CD8 and CD4 T cell responses, and their relative importance depends on the mode of infection in vivo.